Pemanfaatan Museum Bahari Di Jakarta Sebagai Sumber Belajar Sejarah - Novitasari Nurzengky Ibrahim, Corry Iriani (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2024)
This study aims to obtain empirical data about utilization of Museum Bahari in Jakarta as history learning sources for high school students or vocational high school in West Jakarta and East Jakarta. The reason the researcher wrote the research is because it is related to the 2013 Curriculum material, namely learning Indonesian History in regarding the material on the process of entry and development of European colonization basic competencies for 3.5 and 4.5.This study uses a descriptive method with survey techniques through questionnaires. Answers from respondents are described in the form of frequency tabulations or percentages obtained from questionnaires. The Study population was visitors students in class X at SMKN 26 Jakarta, students in class XI at SMKN 60 Jakarta,students in class XII at SMAN 84 Jakarta. With the number of respondents as many as 54 students obtained using cluster random sampling techniques. Based on the results of the study showed that the use of Museum Bahari in Jakarta As History Learning Sources very good. This is supported by data of 100% can help students understand the material. 100% of the collections in Museum Bahari are related to Indonesian learning material during colonialismwhich studied the arrival of Europeans ( Portuguese, Spanish, English, and Dutch) in Indonesian. 72,3% of them stated that no constraint that faced in Utilization of Museum Bahari. So it can be concluded that utilization of Museum Bahari as history learning sources is very helpful in the process of learning history. Keywords: Museum’s Utilization, History’s Learning Resources